2002
DOI: 10.1093/treephys/22.5.321
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic acclimation of overstory Populus tremuloides and understory Acer saccharum to elevated atmospheric CO2 concentration: interactions with shade and soil nitrogen

Abstract: We exposed Populus tremuloides Michx. and Acer saccharum Marsh. to a factorial combination of ambient and elevated atmospheric CO2 concentrations ([CO2]) and high-nitrogen (N) and low-N soil treatments in open-top chambers for 3 years. Our objective was to compare photosynthetic acclimation to elevated [CO2] between species of contrasting shade tolerance, and to determine if soil N or shading modify the acclimation response. Sun and shade leaf responses to elevated [CO2] and soil N were compared between upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 33 publications
2
17
1
Order By: Relevance
“…Studies have found that soil fertility can restrain the plant growth response to CO 2 enrichment (Kubiske et al, 1997;Curtis et al, 2000;Oren et al, 2001;Tissue et al, 2001). Our results further suggest that soil N availability may mediate the acclimation response of photosynthesis to CO 2 enrichment, with low N sites acclimating more to elevated CO 2 than sites having higher fertility (Medlyn et al, 2000, Kubiske et al, 2002. This suggests that the response of ecosystems to enriched atmospheric [CO 2 ] will depend on the nutrient availability of the ecosystem (Saxe et al, 1998;Kö rner, 2000;McMurtrie et al, 2001;Spinnler et al, 2002).…”
Section: Photosynthesissupporting
confidence: 63%
“…Studies have found that soil fertility can restrain the plant growth response to CO 2 enrichment (Kubiske et al, 1997;Curtis et al, 2000;Oren et al, 2001;Tissue et al, 2001). Our results further suggest that soil N availability may mediate the acclimation response of photosynthesis to CO 2 enrichment, with low N sites acclimating more to elevated CO 2 than sites having higher fertility (Medlyn et al, 2000, Kubiske et al, 2002. This suggests that the response of ecosystems to enriched atmospheric [CO 2 ] will depend on the nutrient availability of the ecosystem (Saxe et al, 1998;Kö rner, 2000;McMurtrie et al, 2001;Spinnler et al, 2002).…”
Section: Photosynthesissupporting
confidence: 63%
“…It has been hypothesized that within-canopy differences in the light environment may influence the response to eC (Kubiske et al , 2002) as a result of light-driven differences in photosynthetic N allocation (Evans, 1993; Hikosaka and Terashima, 1995). Although lower canopy leaves showed weaker responses to eC and eT relative to upper canopy leaves, there were no significant canopy×treatment interactions for any of the measured parameters (except for a significant canopy×temperature effect on LMA), probably due to the open crown structure in Eucalyptus species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the inclusion of insect herbivory in a growth chamber experiment altered the lifetime fitness response of Arabidopsis thaliana to elevated CO 2 (Bidart‐Bouzat et al 2005); in other words, herbivory was found to either suppressed or decreased plant fitness enhancements induced by elevated CO 2 per se . Other studies have also demonstrated that plant responses to elevated CO 2 can be influenced by plant‐plant competition, temperature, light, water stress, and nutrients (Bazzaz and Miao 1993; Bazzaz et al 1995; Zhang and Lechowicz 1995; Kellomaki and Vaisanen 1997; Curtis and Wang 1998; Andalo et al 2001; Kubiske et al 2002; Wullschleger et al 2002).…”
Section: Elevated Co2 Effectsmentioning
confidence: 99%